A transition-metal-free multicomponent reaction towards constructing chiral 2H-1, 4-benzoxazine scaffolds. Issue 21 (14th October 2020) - Zhu, Lixiang; Ren, Xiaoyu; Du, Juan; Wu, Jia-Hong; Tan, Jian-Ping; Che, Jixing; Pan, Jianke; Wang, Tianli
Abstract : A transition-metal-free multicomponent cascade reaction of α-halogenated ketones, ortho -aminophenols, and aldehydes using a dipeptide phosphonium salt catalyst was developed for the construction of various 2 H -1, 4-benzoxazines. Abstract : Herein, a transition-metal-free multicomponent cascade reaction of readily available α-halogenated ketones, ortho -aminophenols, and aldehydes using a novel dipeptide-based phosphonium salt catalyst was developed for the efficient construction of various 2 H -1, 4-benzoxazine derivatives with excellent functional-group tolerance. The method represents an unprecedented approach for trapping active 1, 5-bifunctional intermediates with α-halogenated ketones to access biologically important benzoxazine scaffolds bearing two stereogenic centers with excellent asymmetric induction.